DDEL-01. ENHANCING DRUG DELIVERY WITH MRgFUS FOR DIFFUSE INTRINSIC PONTINE GLIOMA MODEL. (4th December 2020) - Ishida, Joji; Alli, Saira; Bondoc, Andrew; Golbourn, Brian; Sabha, Nesrin; Mikloska, Kristina; Srikanthan, Dilakshan; Luck, Amanda; Smith, Christian; Hynynen, Kullervo; Rutka, James
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a surgically unresectable and devasting tumor in children. To date, there have been no effective chemotherapeutics despite a myriad of clinical trials. The intact blood-brain barrier (BBB) in part is responsible for the limited clinical response to chemotherapy. MRI guided focused ultrasound (MRgFUS) is a promising non-invasive tissue ablative method for CNS tumors. Moreover, MRgFUS allows for the temporary disruption of BBB. Our first objective was to determine the feasibility and safety of temporary BBB disruption within the brainstem using MRgFUS following intravenous (IV) administration of microbubbles in vivo. Our second objective was to select effective chemotherapeutics against DIPG cell lines, and to examine their therapeutic effects with MRgFUS in a mouse model of DIPG which exhibits an intact BBB. The non-invasive opening of the BBB was determined in the brainstem of normal rodents using physiological monitoring and histological analysis. Doxorubicin was selected from a drug screen consisting of conventional chemotherapeutics using SU-DIPG4 and SU-DIPG17 cell lines. We established SU-DIPG17 xenografts which demonstrated diffusely infiltrative tumor growth similar to human DIPG. By LC-MS/MS analysis, MRgFUS led to a 4-fold increase in doxorubicin concentrations within the brainstem tumors following IV administration when compared to IV administration alone, We demonstrated feasibility and safety of MRgFUS in the rodent brainstem and have shown that MRgFUS increases doxorubicin uptake in the brainstem of a rodent model of DIPG. These preclinical data will be helpful in designing clinical trials of BBB disruption using MRgFUS for DIPG in children.